Passenger - Bracken, Alexandra (2016)
When a sudden tragedy sends violin prodigy Etta Spencer many miles and many years from home, she finds herself on a ship racing to escape a powerful family from the Colonies. Nicholas Carter, hoping to finally be free, joins the strange new passenger on his ship to keep a stolen object out of the family's clutches. Danger draws near as perilous forces threaten to send Etta and Nicholas off-course
VOYA (Voice of Youth Advocates Magazine)
BookPage
Bulletin of the Center for Children's Books
Booklist
14-19.
9-12.
Keywords: Treasure hunt (Game) -- Juvenile fiction